Strategi Konten Kreatif Pada Media Sosial Instagram Untuk Meningkatkan Popularitas Klub Internal Persebaya Amatir - Sabila Amara Rachma; Supriyono Supriyono (Pakis Journal Institute, 2024)
The widespread use of the internet accessed by the public makes communication via social media an effective way to increase the popularity or fame of an account on social media. The important role of account managers on social media, especially Instagram, is one strategy for forming social media branding for a company, one of which is the football industry. This research aims to determine creative content strategies in increasing the popularity of a club on Instagram social media. The method or approach used in writing this journal is the qualitative descriptive method, where this method has a main focus that uses data acquisition that is as it is. The results of this research journal were obtained from uploading creative content on Instagram social media belonging to the Persebaya internal club in order to increase popularity among social media users, especially Instagram.